Estágio Curricular Supervisionado em Ambientes Virtuais de Aprendizagem - CRUZ, Ediane de Andrade (Universidade Federal do Oeste do Pará, 2024)
Due to the covid-19 pandemic, educational institutions had to adopt a new format for the 2021 academic year and the subjects offered in this period were re-offered in the form of remote classes, including supervised internships. Due to this opportunity, students of the Degree in Educational Informatics (LIE) at the Federal University of Western Pará (UFOPA) had the opportunity to carry out the Supervised Internship III - Virtual Learning Environments/Non-School Environments). The study sought to analyze the impacts of emergency remote teaching on the offer of stage III of LIE/UFOPA to students of the LIE 2017 class, enrolled in semester 2020.1. The research is bibliographical, documentary and empirical, with a qualitative approach. The documents generated from the completion of the internship were the object of documentary study. In the field research, the online questionnaire developed on the Google Forms platform was adopted, containing questions of the Likert scale type, open and closed, applied to students who enrolled the first time the component was offered, however, carried out in the middle of a pandemic and fully on the remote model. The results reveal that despite the difficulties faced by the students, the experience brought a sample of how a professional licensed in Educational Informatics can contribute to different sectors of society, both in the educational scope and in non-school environments. With the results generated through this research, it can be concluded that remote teaching challenged all those involved, as it required dedication and commitment, especially for students who live in cities in the countryside¸ due to the bad infrastructure of the internet network; the students claim that they were able to develop all the activities that were proposed in the pre-established time, with the institutions that received them, thus showing that the professional in Educational Informatics can work in several areas and that digital technology is increasingly present in life people and society in general.